Survei marketing mix diversifikasi olahan tepung buah lokal salak manonjaya bagi pelaku usaha kecil pangan - Sumarto Sumarto; Ani Radiati; Raden Agus Bachtiar (AGROINTEK, 2023)
One of the efforts to increase consumption of fruits and vegetables for the local community and others area is innovate the diversification of processed food products. For example, the fruit of Manonjaya salacca had been researched and made a semi-finished product in the form of flour and other processed food products such as muffins, cakes, cookies, and flakes. Before, the results of the research had been diseminated to the local Small and Medium Enterprises (SMEs). The purpose of this study was to determine the potential development of processed food product from Manonjaya salacca flour diversification for the food SMEs throught a market survey with marketing mix approach. The research method used was a survey with a quantitative approach. The survey was conducted online to 251 respondents throughout Indonesia. Respondents consist of various generations, gender, profession, domicile, and level of income. Questions were given based on the marketing mix categories, namely product, place, price, and promotion. Product: the market survey results show that Manonjaya salak flour has the potential to be developed into souvenirs or sweet snacks for all generations, especially in the Z generation. The product that has the potential to be developed was sponge cake/cake. Place: most of the respondents bought souvenirs in stores, while the millennials and the Z generations bought sweet snacks through online delivery services. Price: respondents stated that a reasonable price for a sweet snack per 750 grams is IDR40,000. Promotion: The further away from the respondent's domicile, the less familiar they were with Manonjaya salacca. For this reason, processed food products from Manonjaya salacca flour need wider promotion. This product promotion is mainly related to the superiority of nutrients, their health benefits, and the variety of diversified products developed by SMEs